Author Correction: The prognostic effects of somatic mutations in ER-positive breast cancer. Issue 1 (December 2018) - Griffith, Obi; Spies, Nicholas; Anurag, Meenakshi; Griffith, Malachi; Luo, Jingqin; Tu, Dongsheng; Yeo, Belinda; Kunisaki, Jason; Miller, Christopher; Krysiak, Kilannin; Hundal, Jasreet; Ainscough, Benjamin; et al.
The original version of this Article contained errors in the depiction of confidence intervals in the NF1 BCSS data illustrated in Figure 3b. These have now been corrected in both the PDF and HTML versions of the Article. The incorrect version of Figure 3b is presented in the associated Author Correction.